Impact of open innovation on globalization: a survey study on China - Chien, FengSheng; Zhang, YunQian; Sadiq, Muhammad (Technological and Economic Development of Economy, 2024)
The objective of this study is to examine the role of open innovation practices to promote globalization. For this purpose, this study considered two open innovation practices: external knowledge and supplier involvement. A survey was carried out to collect primary data from the respondents. This study preferred Chinese small and medium-sized enterprises (SMEs) to examine the role of open innovation in globalization. Data were collected from the employees of SMEs in China. By employing Structural Equation Modeling, this study addressed the important insights for academicians and practitioners. It is concluded that; open innovation practices have key role to promote globalization. The promotion of open innovation practices among the Chinese SMEs can increase the globalization potential. The strategies of open innovation led to increase in business collaboration across the border business organizations. The business collaboration between the SMEs of various countries is the best way to enhance globalization by increasing the level of social capital. Therefore, those institutions who want to promote globalization should promote open innovation practices among the business organizations.